Relationship between Carotid Atherosclerosis and Plasma Endothelin-1 Concentration in Senile Patients with Hypertension - Yamamoto, Yuta; Yamano, Shigeru; Minami, Shigetoshi; Nomura, Kumiko; Nakatani, Akira; Sawai, Nobuyuki; Fukui, Rie; Takaoka, Minoru; Dohi, Kazuhiro (Nihon Rōnen Igakkai zasshi, 1997)
The relationship between carotid atherosclerosis and plasma endothelin-1 (ET-1) concentration was studied in senile patients with essential hypertension. A total of 212 patients (83M, 129F; mean age, 63 years) with essential hypertension (WHO stage I-II), and 109 age-matched control subjects (mean age, 61 years) were enrolled in the study. The maximum thicknesses of the intima-media complex (IMTmax) in the right common carotid artery (CCA) and the right internal carotid artery (ICA) was measured by B-mode ultrasonography, and ET-1 was measured by enzyme immunoassay. ET-1 levels were significantly higher in the hypertensive patients than in the control subjects. In middle-aged patients (35-64 years old), IMTmax values of the ICA in patients with high ET-1 concentrations (ET-≥1.71pg/ml) were significantly higher than in patients with normal ET-1 concentrations (ET-1<1.71pg/ml). However, the IMTmax of the CCA did not show a similar correlation. In senile patients (65-83 years old), both the CCA and ICA IMTmax values were significantly higher in patients with high ET-1 concentrations than in those with normal ET-1 concentrations. These results indicate that high ET-1 levels in middle-aged patients with essential hypertension may play a role in the progression of ICA atherosclerosis. High ET-1 levels in senile patients with essential hypertension may cause progression of atherosclerosis in both the ICA and CCA.